Territorial planning and sustainable development—case study: Protected areas in the territory of the Aspiring West Geopark, Portugal - Dias, Alline; Robina-Ramírez, Rafael; Sánchez-Oro Sánchez, Marcelo (Frontiers in Environmental Science, 2023)
Abstract The holistic concept of sustainable development of UNESCO Global Geoparks encompasses a promotion of connected protected areas and activities that link geological heritage with other aspects of natural and cultural heritage. This case study aimed to identify points of articulation and/or to identify conflicts in the overlap between protected areas and UNESCO World Geoparks in Portugal, and to provide information to improve the interrelation of these designations. The methodological procedures consist of bibliographic and documental research, supported by activities in, carried out between September 2020 and November 2021, for territory recognition and data collection. The study resulted in the identification of points of natural objects that can be held together by the protected natural spaces and aGO. A proposal for synergistic action was presented with the main pillars of integration in the territory. The different designations for sustainable territorial management in complementarity, favoring the conservation of natural heritage. No points of divergence were identified between the criteria of the UNESCO Geoparks Program of the areas originally identified and those already identified in the territory. This reinforcement study, which as different designations of areas and/or territories for sustainable territorial planning, at the local, regional, national, and international levels, are fundamental for nature conservation, lacking more in terms of efficient management and integration of the social component.